Potential role of civil society organizations (CSOs) in antimicrobial resistance (AMR) mitigation efforts in low- and middle-income countries: A report from India - Raghini Ranganathan; Jaya Ranjalkar (Elsevier, 2023)
Antibiotic resistance (ABR) is a global health threat with the potential to cause mortality and morbidity on an unprecedented scale. In the past, civil society organizations (CSOs) have been successful in complementing the efforts of government health systems, thereby shaping the course of various public health programs, especially in low- and middle-income countries (LMICs). This article reports the outcomes of a CSO sensitization workshop held by one of the regional nodes of ReAct and highlights the perspectives of CSOs on their role in supporting the implementation of national and sub-national action plans for AMR mitigation. CSOs can contribute to (i) redefining the AMR narrative, (ii) generating the data for action and policy change, (iii) advocating for policy change, (iv) promoting research and influencing decisions pertaining to research in AMR, and (v) undertaking behavioral change communication for different target groups, among others. Governments in LMICs could leverage the expertise of CSOs by playing the role of facilitator while ensuring that the interventions align with national priorities and are sustainable. Efforts to ensure diverse funding and capacity building among CSOs should happen in parallel to ensure maximum impact on communities.